Zmienność cech morfologicznych, wiosennego pędzenia pąków i kwitnienia świerka pospolitego (Picea abies [L.] Karst.) na plantacji nasiennej w Nadleśnictwie Bielsk - Mioduszewski, Sławomir; Rzońca, Marek (Leśne Prace Badawcze, 2015)
The main aim of this paper was to characterize Norway spruce clones in terms of bud burst, flowering and morphological features. Observation and measurements were carried out in the Norway spruce seed orchard of the Bielsk Forest District in the north-eastern part of Poland. The seed orchard was established in 1989 and consists of 428 grafts of over 37 trees from the Białowieża Primeval Forest. An assessment of bud burst, stem forking, stem form, crown width, branch thickness, vitality, flowering and fructification as well as diameter measurements was done in 2013 and 2014. The results showed variability of morphological features among different clones as well as within individual clones. Differences among clones in spring bud development, stem form and branch thickness were statistically significant. Additionally, a positive correlation between male and female flowering was observed. The research also confirmed an influence of the healthiness of the grafts on seed production with trees in a weakened state producing more seeds.